Eight years of bioethics - Moreno-Exebio, Luis (Acta Bioethica, 2012)
This article presents the experience acquired by participating in the international ethics of biomedical and psychosocial research training program of the Interdisciplinary Center for Studies on Bioethics of the University of Chile (2003-2004) and some reflections about the integration of knowledge acquired in my posterior work at scientific ethical review committees and ethics of research academic programs. Furthermore, in the elaboration of regulations for improving scientific and ethical review.